Integrating Indian Knowledge System into Modern Physical Education: A Meta-Analysis - Dr. Rekha M. Chaudhari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The Indian knowledge system (IKS), originating from ancient scriptures like the Vedas, Upanishads, and the practices of Ashtanga Yoga, offers a unique perspective on the integration of physical, mental, and spiritual aspects of life. While modern physical science has predominantly followed Western paradigms, the Indian system incorporates a holistic approach to understanding the universe, emphasizing the interconnectedness of all elements. This paper explores how the integration of IKS with modern physical education can enhance learning by combining scientific inquiry with spirituality. The Indian system provides valuable insights into atomic theory, cosmology, and the holistic nature of existence, which resonate with modern physics, such as Albert Einstein’s theory of relativity and quantum mechanics. The practices of Yoga and meditation, key elements of IKS, improve concentration, mental health, and coordination, enhancing physical education. This paper argues that integrating these approaches can provide a more comprehensive and global understanding of physical and mental well-being. By embracing both modern scientific methods and traditional Indian wisdom, students can benefit from a balanced development of mind, body, and spirit, fostering a well-rounded educational experience that nurtures both scientific reasoning and spiritual insight.
Keywords: Integrating; IKS; Physical Education